Artificial neural network model for prediction of dynamical behavior in spray boom - Mona, Tahmasebi; Roslan, Abd Rahman; Mohammad Gohari (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.